PENGARUH KOMPETENSI PADA AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Wardhana, Gede Ary Surya; Rasmini, Ni Ketut; Putra Astika, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This research was conducted to examine the performance accountability of government, specifically the government institution of Tabanan regency. The aims of this research are to find out the influence of competency to the performance accountability of government institution and to determine the influence of organizational commitment in strengthening the effects of competency into the performance accountability of government institution. Sampling technique used is saturation sampling . T he respondents as many as 41 people. Secondary data used was obtained from the score of the performance accountability evaluation report of Tabanan regency’s government institution in 2013, while the primary data was obtained through questionnaire. The analyzing technique used is Moderated Regression Analysis. Result of the study indicates that competency positive affects on the performance accountability of government institution while organizational commitment strengthening the influence of competency to the performance accountability of the government institution.
Keywords: performance accountability, government institution, competency, organizational commitment